Probing of Nucleic Acid Structures, Dynamics, and Interactions With Environment-Sensitive Fluorescent Labels - Michel, Benoît Y.; Dziuba, Dmytro; Benhida, Rachid; Demchenko, Alexander P.; Burger, Alain (Frontiers in Chemistry, 2020)
Fluorescence labeling and probing are fundamental techniques for nucleic acid analysis and quantification. However, new fluorescent probes and approaches are urgently needed in order to accurately determine structural and conformational dynamics of DNA and RNA at the level of single nucleobases/base pairs, and to probe the interactions between nucleic acids with proteins. This review describes the means by which to achieve these goals using nucleobase replacement or modification with advanced fluorescent dyes that respond by the changing of their fluorescence parameters to their local environment (altered polarity, hydration, flipping dynamics and formation/breaking of hydrogen bonds).